Effects of Light Quality on Vegetative Growth and Flower Initiation in Phalaenopsis - Dewi, Kumala; Purwestri, Yekti Asih; Astuti, Yohana Theresia Maria; Natasaputra, Lila; P, Parmi (Universitas Gadjah Mada, 2014)
The effects of LEDs (Light-Emitting Diodes) emitting different colours namely red, blue, red andblue, and white lights on vegetative growth and fl ower initiation of Phalaenopsis have been evaluated.Phalaenopsisâotohine/taisuco fi re birdâ seedlings in vitro were subjected to different light qualities for either2 or 4 weeks, and then each seedling was planted in a plastic pot containing sphagnum and grown in thegrowth chamber under similar light quality for 3 months. For fl ower induction, mature Phalaenopsis plantshaving 4 â 6 leaves were grown for 3 months in the growth chamber under different light qualities. The leafspan, chlorophyll, gibberellin and cytokinin content were determined. In addition, the expressions of FT-likegene in the leaf, axillary bud, fl ower bud and stalk were examined.Vegetative growth was enhanced under blue, red-blue or white LEDs compared to that of the control.Gibberellin and cytokinin content increased in the seedlings subjected to white LEDs. Based on the averageof leaf span increment it was suggested that the growth of Phalaenopsis seedlings can be promoted by givingeither blue, red-blue or white LEDs. From the second experiment, it was found that fl ower induction inPhalaenopsis can be obtained in plants that had just fi nished fl owering without the application of LEDs. Theexpression of FT-like gene in the leaf as well as fl ower bud and stalk suggests that this gene is involved infl ower regulation of Phalaenopsis.